Tingkat Pengetahuan Dan Sikap Ibu Balita Tentang Gizi Terhadap Kejadian Stunting Di Desa Belang Turi, Manggarai,NTT - Putriatri Krimasusini Senudin (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Infants are the most vulnerable group of a society to stunting. In Indonesia the prevalence of stunting infants is 30.8%, while the NTT Province is 46.2% in 2018. Stunting can inhibit physical growth, mental development and health status of children. This study aims to determine the relationship of mother's knowledge about nutrition and their attitudes to stunting. This quantitative study with a descriptive correlation method applied a cross-sectional approach. There were 68 mothers who involved in the present study and were selected by simple random sampling. The instrument used was a closed questionnaire and analyzed by Chi-square test. The results of this study indicate that the level of knowledge of infants' mothers about nutrition is mostly moderate (45.6%), their attitudes on stunting are mostly unfavorable by 35%. Moreover, there is a relationship between infants' mothers knowledge about nutrition and their attitudes on stunting with p- value = 0.00. Having taken into account about the findings of the present study, it is hoped that the mothers of infants can increase their knowledge about nutrition to reduce the stunting case in order to create a healthy generation.